Met-Flow analyses of the metabolic heterogeneity associated with different stages of cord blood-derived hematopoietic cell differentiation - Zhang, Sen; Kong, Xiaodong; Yao, Ming; Qi, Jinfeng; Li, Ying; Liang, Haoyue; Zhou, Yuan (Frontiers in Immunology, 2024)
Background: The differentiation of hematopoietic cells is significantly affected by cell metabolic activity. However, despite increasing interest in this field, there has been no comprehensive investigation of the metabolic functions of human hematopoietic cells during specific phases of differentiation. Thus, this study was conducted to develop a method for comparing hematopoietic cell lineage differentiation based on the metabolic functions of the cell. The metabolic activity of human umbilical cord-derived hematopoietic cells was examined during various phases of differentiation, specifically, hematopoietic stem cells (HSCs), hematopoietic progenitor cells, and differentiated blood cells. This approach was used to develop comprehensive metabolic maps corresponding to the different stages. Results: HSCs were found to have robust fatty acid (FA) synthesis, FA oxidation, pentose phosphate pathway (PPP) activity, and glucose uptake, shown by their significantly higher expression of ACAC, CPT1A, G6PD, and GLUT1 as compared to differentiated pluripotent progenitor cells, common myeloid progenitors, megakaryocyte erythroid progenitors, lympho-myeloid primed progenitors, and granulocyte-macrophage progenitor cell populations. In monocytic differentiation, higher levels of ACAC, ASS1, ATP5A, CPT1A, G6PD, GLUT1, IDH2, PRDX2, and HK1 protein expression were evident in classical and intermediate monocytes relative to non-classical monocytes, consistent with high anabolic and catabolic levels. Compared with myelocytes and mature cells, the meta-myelocyte and pro-myelocyte populations of granulocytes show significantly elevated levels of ACAC, ASS1, ATP5A, CPT1A, G6PD, IDH2, PRDX2, and HK. In contrast to naïve and regulatory B cells, pro-B cells had higher levels of oxidative phosphorylation, while regulatory B cells showed greater PPP activity, glucose uptake, and tricarboxylic acid cycle activity. The analyses of T cells also indicated significantly higher ACAC, ASS1, ATP5A, CPT1A, G6PD, GLUT1, IDH2, PRDX2, and HK1 expression levels in CD4+ populations compared with CD8+ populations. Conclusions: The results provide comprehensive analytical methods and reference values for future systematic studies into the metabolic functions of various cord blood-derived hematopoietic cell populations in different pathological or physiological conditions. These findings could also contribute to research on the connection between cellular metabolism and cancer or aging.